Internalización de la Teoría de las Inteligencias Múltiples Mediante el Uso de una Propuesta Pedagógica Diseñada Para Docentes (2024)
The present work tries to be a contribution from Psychology, to improve the quality of Preschool Education. It is a strategy that seeks to change in the teacher the generalized but limited concept that relates intelligence only to those logical-mathematical or linguistic abilities, and that does not review other abilities that a boy or a girl may have. By not taking other abilities into account, the child who does not have logical-mathematical and/or linguistic abilities is most likely labeled as not very intelligent. This kind of premature labeling that can originate in the mind of the teacher, is quite harmful for the infant as their self-esteem and subsequent academic performance flourish (Rosenthal, 1964). Universally endorsed experiments, such as "the Rosenthal experiment" (Baths, page 1), demonstrate this. The strategy for teaching change includes the construction of a pedagogical model to apply directly in the classroom and which consists of a well-developed selection of existing didactic games that will allow the teacher, considering Dr. Howard's Multiple Intelligences theory, apply and qualify in real time —through an App— the individual performance of their students without requiring additional effort to their normal workload. At the end of the application of the proposed pedagogical model and having automatically generated a graph on the multiple intelligences that each of his students possesses, we hope to produce the desired transformation in the teacher's pedagogical practice; we will bring you closer to cutting-edge psychological theories, we will contribute to improving the quality of preschool education and we will protect the child's nascent self-esteem.